Emodin Alleviates Severe Acute Pancreatitis-Associated Acute Lung Injury by Inhibiting the Cold-Inducible RNA-Binding Protein (CIRP)-Mediated Activation of the NLRP3/IL-1β/CXCL1 Signaling - Qiushi Xu; Qiushi Xu; Mengfei Wang; Mengfei Wang; Haoya Guo; Haoya Guo; Huanhuan Liu; Huanhuan Liu; Guixin Zhang; Guixin Zhang; Caiming Xu; Caiming Xu; et al. (Frontiers Media S.A., 2021)
Objective: Severe acute pancreatitis (SAP) can lead to acute lung injury (ALI). This study investigated the therapeutic effect of emodin and its molecular mechanisms in a rat model of SAP-ALI.Methods: Forty male Sprague-Dawley rats were randomly divided into the groups: Control (CON), SAP (SAP), emodin (EMO), and C23 (C23). The latter three groups of rats were induced for SAP-ALI by retrograde injection of 5% sodium taurocholate into the biliary-pancreatic duct and were treated with vehicle, emodin or C23, respectively. One day post induction, their pancreatic and lung injury was assessed by histology and arterial blood gas analysis. In vitro, rat alveolar macrophages (NR8383 cells) were treated with recombinant rat CIRP in the presence or absence of TAK242 (a TLR4 inhibitor), C23 or emodin. The CIRP-mediated activation of the NLRP3/IL-1β/CXCL1 signaling in rat lungs and NR8383 cells was determined. Similarly, the role of IL-1β in the CIRP-induced CXCL1 expression was investigated.Results: Emodin treatment significantly reduced inflammation and tissue damages in the pancreatic and lung tissues in rats with SAP-ALI, accompanied by decreasing serum amylase, CIRP and IL-1β levels and improving lung function. Furthermore, emodin significantly mitigated the SAP-up-regulated CIRP expression in the pancreatic islets and lung tissues, and attenuated the SAP-activated NF-κB signaling, NLRP3 inflammasome formation and CXCL1 expression in lung resident macrophages as well as neutrophil infiltration in the lungs of rats. In addition, treatment with CIRP significantly activated the NF-κB signaling and NLRP3 inflammasome formation and induced IL-1β and CXCL1 expression and pyroptosis in NR8383 cells, which were abrogated by TAK242 and significantly mitigated by C23 or emodin. Moreover, CIRP only induced very lower levels of CXCL1 expression in IL-1β-silencing NR8383 cells and treatment with IL-1β induced CXCL1 expression in NR8383 cells in a dose and time-dependent manner.Conclusion: Emodin may inhibit the CIRP-activated NLRP3/IL-1β/CXCL1signaling to decrease neutrophil infiltration and ameliorate the SAP-ALI in rats.